2007
DOI: 10.1038/sj.bmt.1705566
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of umbilical cord serum eyedrops for the treatment of dry eye associated with graft-versus-host disease

Abstract: This study was performed to investigate the therapeutic effect of umbilical cord serum eyedrops on dry eye associated with graft-versus-host disease (GVHD). Twenty-four eyes of 12 patients with severe dry eye syndrome associated with GVHD were treated with 20% umbilical cord serum eyedrops. Symptom scoring, corneal sensitivity test, tear film break up time (BUT), Schirmer test, tear clearance rate (TCR), and corneal fluorescein staining were performed before and 2 and 6 months after treatment. Six months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 17 publications
1
44
2
4
Order By: Relevance
“…Unquantifiable reflex secretion following the insertion of Schirmer strips makes it difficult to assess the agreement of our findings with previous reports of Schirmer test results in cGVHD. The general trend observed with cGVHD dry eye patients was of low Schirmer test values, 2,7,8,14,20,21 supporting the impairment of tear production in cGVHD-associated dry eye. A histological study has shown that there is a predominant infiltration of T-cells into the periductal area, an increase in the number of stromal fibroblasts and excessive fibrosis in Although no statistically significant differences were found, the data indicates that the tear osmolarity values for cGVHD-associated dry eye are higher than that for the other groups.…”
Section: Discussionmentioning
confidence: 97%
“…Unquantifiable reflex secretion following the insertion of Schirmer strips makes it difficult to assess the agreement of our findings with previous reports of Schirmer test results in cGVHD. The general trend observed with cGVHD dry eye patients was of low Schirmer test values, 2,7,8,14,20,21 supporting the impairment of tear production in cGVHD-associated dry eye. A histological study has shown that there is a predominant infiltration of T-cells into the periductal area, an increase in the number of stromal fibroblasts and excessive fibrosis in Although no statistically significant differences were found, the data indicates that the tear osmolarity values for cGVHD-associated dry eye are higher than that for the other groups.…”
Section: Discussionmentioning
confidence: 97%
“…10,[13][14][15] The efficacy and safety of serum eye drops for dry eye disease in patients with cGVHD have been previously investigated. 14,[16][17][18] However, autologous serum may be unavailable for patients with cGVHD, because Asians commonly believe that frequent venipuncture results in general weakness or increases the risk of bacterial infection. For these patients, practitioners suggest the use of allogeneic serum eye drops from related donors as an alternative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…16 Yoon et al also reported that in 12 patients with ocular GVHD, use of umbilical cord serum eye drops resulted in a therapeutic effect. 18 However, autologous serum is not available when patients have active systemic inflammation, fear of venipuncture, and if they are infants or elderly. Frequently, patients with ocular GVHD have cGVHD in locations other than the eyes, and in those cases, poor systemic conditions such as malnutrition or dyspnea can cause patients to hesitate in using autologous serum for the treatment of dry eye disease.…”
mentioning
confidence: 99%
“…20 Keratoepitheliopathy was scored by multiplying the area score (0-3) by the density score (0-3) after staining with 1% fluorescein dye. 21 Subjective symptoms such as burning, dryness, and foreign body sensation were graded on a numerical score of 0 to 4, with 0 representing no symptom and 4 representing very severe symptoms that caused discomfort and interfered with normal activities. 8,22 Statistical Analysis SPSS version 12.0 (SPSS, Chicago, IL) was used for statistical analyses.…”
Section: Postoperative Treatmentmentioning
confidence: 99%